1978
DOI: 10.1136/jcp.31.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Measuring IgG anti-A/B titres using dithiothreitol (DTT).

Abstract: SUMMARY In comparing the use of the sulphydryl compounds 2-mercaptoethanol (2ME) and dithiothreitol (DTT) a rapid one-stage technique for titrating IgG anti-A and anti-B using DTT in an antiglobulin test was tried. The results correlated well with those obtained by either of the two-stage methods using 2ME or DTT. Bowley (1969) showed that the anti-A/B titre determined by a spin antiglobulin technique after 2ME inactivation correlated well with clinical severity in cases of ABO HDN, a titre of more than 1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…It has been shown that anti-A agglutinins treated with sulphydryl compounds would inhibit agglutination although the treated agglutinin no longer agglutinates the cells. Similarly, they are shown to give a positive antiglobulin test with appropriate cells (Moore and Steane, 1976;Knight, 1978). It is interesting to note in our studies (Table 4) that no changes of scores (neither increase nor decrease) are observed in the antiglobulin phase of reaction after DTT treatment.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It has been shown that anti-A agglutinins treated with sulphydryl compounds would inhibit agglutination although the treated agglutinin no longer agglutinates the cells. Similarly, they are shown to give a positive antiglobulin test with appropriate cells (Moore and Steane, 1976;Knight, 1978). It is interesting to note in our studies (Table 4) that no changes of scores (neither increase nor decrease) are observed in the antiglobulin phase of reaction after DTT treatment.…”
Section: Discussionsupporting
confidence: 62%
“…There appears to be disagreement regarding the optimal conditions, such as incubation period, incubation temperature, or pH, for the 2-mercaptoethanol method of inactivating IgM antibodies (Freedman et al, 1976), and only a few studies on dithiothreitol reagent are available in the literature (Pirofsky and Rosner, 1974;Knight, 1978). The procedure for DTT is generally the one described by Pirofsky and Rosner.…”
Section: Discussionmentioning
confidence: 99%
“…DTT treatment is needed to measure the exact IgG titration. However, the process for DTT treatment is cumbersome, time consuming, and may destroy IgG [ 14 ]. According to the 'uniform procedure' for ABO Ab titration suggested by the College of American Pathologists, the tube test can be converted to the AHG phase after 30 min of RT incubation without DTT treatment [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dilution process was same as that for IgM. After incubating for 30 min in a 37°C water bath , 100 µl of 2% type A1 blood cell suspension or type B blood suspension (Ortho‐Clinical Diagnostics, High, Wycombe, UK) was dispensed into each tube and incubated for another 30 min in a 37°C water bath. The mixture was processed with the UltraCW automatic cell washing system (Helmer, Noblesville, USA) four times, and two drops of anti‐globulin reagent (Millipore, Livingstone, UK) were added and the sample was centrifuged for 15 s at 1000 g and then interpreted (Tube IgG).…”
Section: Methodsmentioning
confidence: 99%